The influence of the work environment, financial rewards and type A personality on the choice of a public accountant career (a case study of UKSW FEB Salatiga Accounting Students) - Rerung, Faneshia Tangke; Ashedica pesudo, David Adechandra (International Journal of Social Science and Business, 2021)
The influence of work environment, financial rewards and personality type A on the choice of a public accountant career. This research aims to determine the effect of the work environment, financial rewards, and type A personality on the choice of a public accountant career. The subjects of this study were accounting students, Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana class of 2017 and 2018. This study used a quantitative approach with a linear regression testing method. The sample of this study was 182 respondents. 79 respondents obtained the distribution of data acquisition from the 2017 class and 103 respondents from the 2018 batch. The data was obtained by distributing questionnaires through the google form. Based on the t-test, it can be concluded that the work environment has a positive effect on the choice of a public accountant career, financial rewards have no effect on the choice of a public accountant career, and type A personality has a positive effect on the choice of a public accountant career.